Impact of Body Mass Index on Complication Rates Following Primary Total Ankle Arthroplasty - Weston E. McDonald BS; Ronit Kulkarni BS; Joshua L. Morningstar BS; Richard J. Friedman MD, FRCSC; Daniel J. Scott MBA, MD; Christopher E. Gross MD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: Recent literature has indicated higher body mass index (BMI) to be of concern for poorer outcomes following total ankle arthroplasty. The purpose of this study is to evaluate the impact of implementing BMI cutoff points on 6-month postoperative outcomes following total ankle arthroplasty (TAA). Methods: The Nationwide Readmissions Database (NRD) was queried from 2015-2020 to identify 5,865 patients undergoing primary elective TAA with a reported BMI range via ICD-10 diagnosis. Our cohort consisted of patients with BMI ≥30 kg/m 2 , stratified into groups by 5 BMI point intervals. Preoperative demographics, comorbidities, postoperative outcomes, and total length of stay (LOS) were analyzed between cohorts. Multivariate regression analyses were conducted to control for predictors of adverse postoperative outcomes other than BMI. Results: When stratifying by preoperative BMI, higher BMI was associated with significantly lower age (p <.001) and rate of smoking (p <.001), and higher rate of female sex (p <.001), Medicaid insurance (p <.001), higher CCI score (p <.001), among other comorbidities. Multivariate regression analysis of 180-day postoperative outcomes, controlling for demographic and comorbidity differences, found that preoperative BMI 40-44.9 and ≥45 kg/m2 was significantly predictive of increased risk of any complication (44-44.9: OR=1.843; p<.001)(45+: OR=1.960; p<.001), adverse discharge (44-44.9: OR=1.217 p=.015)(45+: OR=2.030; p<.001), and extended stay greater than 4 days (44-44.9: OR=1.653; p<.001)(45+: OR=2.171; p<.001), with BMI ≥45 kg/m2 also being significantly predictive of 65% increased risk of readmission (OR=1.655; p=.004). Conclusion: Higher BMI in TAA is associated with an increased risk of any postoperative complication, adverse discharge, and extended LOS. Specifically, a BMI cutoff of 40kg/m 2 would serve to prevent 38.6% of the 963 obese patients experiencing complications following TAA. While our results suggest that implementing a strict BMI cutoff would serve to reduce complications substantially, it will also prevent a large number of patients from undergoing a complication-free surgery that will ultimately serve to reduce pain and increase function. Instead, we suggest physicians consider a BMI cutoff in concert with other comorbidity factors that may affect surgical outcomes following TAA.